Effect of Aerobic Exercise on Rehabilitation of Autistic Child - Muhammad Saad Shafiq, Summaiyah Obaid, Iqra Imtiaz, Sundus Nawaz, Kashaf Nadeem, Iqbal Tariq, Farooq Mirza, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the effect of aerobic exercises on cardiopulmonary endurance among Autistic child of different age groups. Methodology: The study was RCT The sampling technique used was Non-probability convenient technique for selection then randomization was done through lottery method. The sample size of 30 was divided into two groups Group A and Group B. Group A was asked to perform stationary cycling for 5 minutes or as per their schedule of daily activities and Harvard step test. Group B was asked to perform Stationary cycling for 10 minutes with warm-up and cool-down for 5 minutes each before and after exercise. Non parametric test was applied for results. Results : comparison of both groups showed Significant improvement in sBP, dBP, HR post training and stationary cycling speed shown significant improvement on week 5 with P value <0.05. Harvard step test post training showed significant difference with P value <0.05. CARS showed significant improvement post training in Experimental group. Conclusion: In this study it was concluded that stationary cycling and Harvard step test are beneficial in order to manage maladaptive behavior of autism spectrum disorder. Stationary cycling with warm up 5 minutes and cool down 5 minutes protocol and Harvard step test are less demanding exercise protocol to increase cardio-respiratory fitness. There was increase in Lung volume capacities after exercise protocol. Keywords: Autism, CARS, Harvard step test, sBP, dBP